Pengaruh Budaya Organisasi, Motivasi Karyawan Dan Komitmen Terhadap Peningkatan Kinerja Karyawan PT. Trans Trijaya Samudera - Eeb Basuni; Irvandi Gustari; Fahruddin Salim (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
This study aims to analyze the influence of organizational culture, employee motivation and employee commitment to improving employee performance at PT. Trans Trijaya Ocean. The sample of this study is the entire population by taking a sample of 50 employees of PT.Trans Trijaya Samudera. Overall, the results of this study indicate that employee motivation has a positive and significant effect on employee performance. Employee motivation has a positive and significant effect on employee commitment, organizational culture, employee motivation and commitment to improving employee performance.